The Stages of Spiritual Life: Joseph Ḥazzāyā and the Greek Spiritual Legacy - Havrylyk, Ihnatia (Vox Patrum, 2019)
For the Assyrian Church of the East, the 5th century became a turning point, which somewhat changed the spiritual and theological face of this Church. It marked the beginning of translations of the philosophical texts and works of the Greek Fathers from Greek into the Syriac language. Some elements of the Greek spirituality gradually penetrated into the Syriac monastic environment, leaving its imprint on it. This article presents a panoramic view of the influence of the Greek ascetic tradition on the Syriac spirituality, as exemplified by the teachings of Joseph Ḥazzāyā, a spiritual author of the 8th century, who is considered to be a systematizer of all Syriac spiritual and mystical experiences. The teaching of Ḥazzāyā was, without a doubt formed, on the basis of his own Syriac tradition, as well as under the influence of great spiritual authorities of other traditions: Evagrius of Pontus, Macarius of Egypt, and John of Apamea. From them, Joseph borrowed the key concepts of his doctrine, formulating it for the first time in the so-called three-stage synthesis of spiritual life, covering various elements that are analyzed in this article.